Analisis Semiotik Roland Barthes pada Film Animasi Nussa dan Rara Episode 1 sampai 5 - Santoso, Imam; Irwansyah, Irwansyah (Journal of Communication Studies, 2023)
Currently, da'wah activities are not only carried out using conventional media, but also use other media such as social media and the internet, one of which is the social media YouTube, a social media that shows the animated series Nussa with an Islamic theme. This research aims to find out what Islamic values ​​are contained in the animated series Nussa episodes 1-5. The type of research used is descriptive qualitative research. The analytical method used is Roland Barthes' semiotic analysis method. Data collection techniques are carried out using observation and documentation. Meanwhile, the data analysis technique is Roland Barthes' semiotic analysis. Barthes' theory divides signs based on signifier and signified then produces denotation, connotation and myth. The Islamic values ​​or da'wah messages contained in each film episode can be identified as elements of da'wah after being analyzed using Roland Barthes' theory. The overall results of this research found that the message of da'wah or Islamic values ​​contained in each episode of this film is courage, cleanliness, manners or ethics, helping others, giving charity, conveying knowledge, sincerity. Which are grouped based on the main aspects of Islamic values, namely moral values, aqidah values ​​and sharia values.